SECULAR TRENDS IN THE DIAGNOSIS AND MANAGEMENT OF TURNER SYNDROME: A SINGLE CENTRE 20-YEAR EXPERIENCE - Morthy, Sasirekha Krisnan; Selveindra, Nalini M; Hong, Janet Yeow Hua; Idris, Arini Nuran (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Turner syndrome (TS) is a sex chromosome disorder with one intact X chromosome and complete or partial absence of the second chromosome. It often involves multiple organ systems, predominantly various endocrinopathies, through all stages of life. METHODOLOGY We performed a descriptive cross-sectional study in the Pediatric Endocrinology Unit Hospital Putrajaya. We retrieved records of all patients with TS managed in our unit between January 2005 and March 2025 from the electronic database system. RESULT Over the past two decades, our unit has treated 72 patients with TS, with monosomy X being the most common karyotype abnormality, affecting 40 patients. In the first decade, from 2006 to 2015, the median age at diagnosis was 5 years (IQR: 0.2 – 10.7 years). 63.3% (n = 19) were diagnosed during childhood, with short stature being the most common presenting complaint. The median age of referral to our unit was 9.5 years (IQR: 4.8 – 12.1). 83% (n = 25) had received recombinant growth hormone treatment (rhGH), and the median age at initiation of rhGH therapy was 11.1 years (IQR: 7.0 – 13.3). The median age of pubertal induction was 14.6 years (IQR: 13.1 – 15.3). In contrast, during the second decade, from 2016 to 2025, patients were diagnosed earlier, with a median age of 2.6 years (IQR: 0.2 – 10.6). Notably, 54.7% (n = 23) were diagnosed antenatally or during infancy due to typical TS features. However, the median age at referral was 7.7 years (IQR: 4.0 – 11.6). During this period, 45.2% (n = 19) began rhGH treatment, with the median age for initiation at 9.0 years (IQR: 5.7 - 11.3). The median age for pubertal induction was 13.8 years (IQR: 13.6 – 14.8). All the patients underwent complete screening for associated abnormalities. CONCLUSION Referrals to a paediatric endocrinologist for Turner Syndrome are often delayed due to a lack of awareness of its various endocrinopathies. Early recognition of its salient features and prompt referral allows for timely intervention and management, predominantly growth hormone and sex hormone treatment, ultimately improving quality of life.